(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In Lithuania, as well as all over the world in developed countries, the society is starting to become a new kind of the information society. Under modern conditions it is increased the role of educated personality, personality capable of not only absorb the previously accumulated knowledge, but also to summarize, analyze, develop new and innovative ideas, information technologies, services and products. Implementing the EU common agricultural and rural development policy and adapting it to the local conditions, special attention must be paid to the qualitative aspects of human capital and education. Environment protection problems are deeply rooted in. The extensive agricultural policy of EU is in active formation process as a serious counterweight and feasible alternative to intensive, almost industrial farming [1]. According to this policy, farmers are supported for reducing negative impact on the environment and fostering an attractive landscape; therefore it is important to develop professional qualification. It is possible to distinguish three forms of education in formation of farmers' human resources: formal, non-formal and informal learning [2]. Formal education takes place in accordance with the statutory procedure, approved and registered training programs witch lead to the acquisition of a primary, secondary, or higher non-university education and qualifications. Non-formal education is learning through a range of educational needs, training, and acquisition of additional skills. It typically involves workshops, community or interest based courses, conference style seminars. Informal education is continuous self-learning, based on the person gaining knowledge from various sources and practical experience. Non-formal and informal education is relevant to farmers who already have some formal education and seek to continually enhance and update their knowledge. Professional development is important to the farmer during all the farming period. The paper deals with environment protection competencies and qualification development gained during non-formal education course of farming basics. The study found out environment protection motivation and tendencies of knowledge use in practical activities.